American lake nuclear peril in the Pacific - Bello, Walden F.; Hayes, Peter; Zarsky, Lyuba (Manila Popular Book Store [distributor], 1986)
"American Lake reveals the precarious state of the American and Soviet nuclear stand-off in the Pacific. It exposes to public view for the first time the full extend of the nuclear arms race in the Pacific - a race which could trigger a global nuclear war. Using previously undisclosed and formerly classified Pentagon files, American Lake shows how World War III could start in the Pacific rather than Europe or the Middle East. Written by the authors who discovered Australia?s role in the MX missile tests, American Lake will frame the debate over the arms alliance for years to come. American Lake argues that nuclear war is not inevitable. It charts a course towards peace."--Back cover.
Part I. Manifest destiny -- 1. The new order in the Pacific -- 2. The Korean watershed -- 3. New look at the nuclear brink -- 4. Nuclear overkill -- 5. Nuclear war by the book -- 6. Losing the war, winning the peace -- 7. Resurgent rollback -- 8. New militarism -- Part II. Pacific arsenals -- 9. Deadly connection -- 10. Pacific command -- 11. The invisible arsenal -- 12. The means of annihilation -- 13. Pacific missile test laboratory -- 14. Missile in search of a mission -- 15. Exercise of power -- 16. The Soviet "threat" -- 17. "Socialist bomb" -- 18. States of terror -- 19. Nuclear epitaph? -- Part III. Charting a new Pacific -- 20. Charting a new Pacific.
A reprint of the same ed. published by Penguin Books, Ringwood, Vic., Australia.
Keywords: Nuclear warfare; Indian Ocean Region -- Strategic aspects -- History; Pacific Area -- Strategic aspects -- History; United States -- Military policy